Direct medical costs of COPD diagnosis and treatment, Eastern vs Western European country – examples of Serbia and Belgium - Jakovljevic, Mihajlo B; Lazic, Zorica; Verhaeghe, Nick; Jankovic, Slobodan; Gajovic, Olgica; Annemans, Lieven (Farmeconomia. Health economics and therapeutic pathways, 2013)
OBJECTIVE: Comparison of COPD financial burden and underlying factors, between Eastern upper middle income and a Western European high income, healthcare settings. METHODS: The patient sample was 433 in Belgium and 322 in Serbia, age ≥ 40, with spirometry and clinically confirmed COPD diagnosis. Belgian trial followed patients prospectively during 2006, using structured survey of clinicians in charge. Serbian trial conducted in 2008, retrieved data from clinical invoice database. Time horizon was one year and perspective of third party payers was taken into account for both studies. Clinical outcomes of interest were disease exacerbation, hospital admission and death. Economic inputs referred to COPD-attributable medical services consumption value during observed period of time. RESULTS: Average annual cost was 1,812.84 € for the Serbian patients and 1,738.13 €/year for the Belgian patients (not including the value of laboratory diagnostics or imaging techniques). Severity grade and duration of hospital admissions significantly directly correlated with overall cost in both populations. Pattern of diagnostic procedures requested and ATC classes of drug consumed to treat COPD remains similar and comparable in both countries. GDP per capita ratio in respective years (10.4: 37.4), exhibits the paradox of patient being much less affordable to treat in a less developed society. CONCLUSIONS: Burden of COPD in Europe is huge and, due to contemporary life style expected to grow further. We compared cost of illness structures between two societies with different macroeconomic past in healthcare financing and management. According to our findings, direct medical costs were driven by exacerbations and hospital admissions. Significantly cheaper human labor caused higher relative relevance of drug acquisition expenses in the East and higher portion of hospital admission costs in the West. More in-depth research of indirect COPD attributable costs (e.g. lost productivity, absenteeism, premature death etc) will be needed in future. It implies serious health policy necessities to provide accessibility of care.